Wall Street capitalism as "the model" for market economies - Ellerman, David P. (Teorija in praksa, 2012)
Throughout much of the world today, American-style Wall Street capitalism is taken as "the model" for a private property market economy. Yet, the Crisis of 2008 has caused some rethinking. This paper argues that far from being "the model," Wall Street capitalism institutionalizes irresponsibility, whereas markets are supposed to connect actions and the responsibility (positive or negative) for those actions. The mother of all the disconnects between action and responsibility is the absentee ownership of business corporations through the stock market. The basic solution is to re-constitute the corporation so that the "human association which in fact produces and distributes wealth" becomes the "association recognised by the law" as being the legal corporation.
Keywords: Capitalism; Kapitalizem; Lastništvo; Ownership; Korporacije; Corporations; Responsibility; Odgovornost; tržno gospodarstvo